Advancing toward normal operations for arenas and stadiums - Parker, J.; Boles, C.; Leleck, O.; Buerger, A.; Egnot, N.; Sundermann, A.; Bussmann, E. (Toxicology and Industrial Health, 2020)
The reopening of arenas and stadiums following closures due to the 2019 coronavirus disease (COVID-19) pandemic presents unique challenges related to large crowds and close contact between players, vendors, and spectators. While each venue should be assessed individually for development and implementation of reopening plans, the general guidance presented in this document can serve as a minimum baseline for considerations to reduce the risk of COVID-19 transmission in these venues. The intention of these guidelines is to provide a layered approach to risk mitigation for various aspects of particular concern in arenas and stadiums, including crowd management, tailgating and parking, restrooms, high-contact surfaces, face masks, food and merchandising, communications, athletes and support staff, press and third parties, intermissions/breaks, and downtime. The implementation of these multifaceted approaches in each area of concern, along with the integration of regulations and requirements from local, state, and federal government bodies and agencies, will reduce the risk of a single point of failure and offer some protection to those at arenas and stadiums from COVID-19 transmission. The approaches outlined are dynamic and should be regularly reviewed and revised as new information becomes available regarding the transmission of COVID-19.